Immunological defence mechanisms of the gastrointestinal tract. - Jewell, D (1984)
The local immune system is highly complex. The distribution of T-cell subsets between epithelium and lamina propria is not random and may be determined by the micro-environment provided by the expression of the class I and II HLA antigens. Macrophages in the small intestine appear to have the characteristics of antigen-processing cells, whereas colonic macrophages may predominantly be phagocytic cells. Suppression of a systemic immune response by prior oral ingestion of antigen may be mediated by cellular and humoral mechanisms. The relation between these mechanisms and the anatomical distribution of lymphocytes within the mucosa is an interesting but unexplored field. The local humoral response is IgA. This is determined by the specific localization within the lamina propria of B-cells sensitized within Peyer's patches while already committed to IgA production. Modulation of this commitment to IgA synthesis may be mediated by a distinct subset of T-cells. In order to resist proteolysis, secretory IgA and IgM become bound to secretory component, which acts uniquely as a receptor and as a transporting protein through the enterocyte. All these mechanisms are presumably aimed at preventing antigen from stimulating injurious immune responses, either locally or systemically. Disturbances in regulation, function or numbers of the immune cell populations may have potential implications for human disease.